2014
DOI: 10.1016/j.jalz.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

A phase1 study of stereotactic gene delivery of AAV2‐NGF for Alzheimer's disease

Abstract: This trial provides important evidence that bilateral stereotactic administration of AAV2-NGF to the nucleus basalis of Meynert is feasible, well-tolerated, and able to produce long-term, biologically active NGF expression, supporting the initiation of an ongoing multicenter, double-blind, sham-surgery-controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 193 publications
(139 citation statements)
references
References 50 publications
2
132
0
Order By: Relevance
“…In a small phase I clinical study (8 patients) reported in 2005, transfected fibroblasts with permanent expression of NGF were implanted in the forebrain of the patients, and significant increase in neuronal activity was reported (179). Also, a more recent Phase I clinical study with ex vivo gene delivery to AD patients demonstrated enhanced cerebral metabolism and cognitive function without significant adverse effects (180). Positron emission tomographic (PET) scans confirmed the inhibition of the metabolic decline expected in AD patients.…”
Section: Nerve Growth Factormentioning
confidence: 99%
“…In a small phase I clinical study (8 patients) reported in 2005, transfected fibroblasts with permanent expression of NGF were implanted in the forebrain of the patients, and significant increase in neuronal activity was reported (179). Also, a more recent Phase I clinical study with ex vivo gene delivery to AD patients demonstrated enhanced cerebral metabolism and cognitive function without significant adverse effects (180). Positron emission tomographic (PET) scans confirmed the inhibition of the metabolic decline expected in AD patients.…”
Section: Nerve Growth Factormentioning
confidence: 99%
“…While much progress is clearly being made in the field of non-viral gene delivery, clinical trials involving viral delivery of genes such as NGF [225], glutamic acid decarboxylase [226], neurturin [227] (a structural relative of GDNF), and ProSavin (tyrosine hydroxylase, AADC, and cyclohydrolase 1) [228] to the brain are providing mounting evidence for the safety of such therapeutic strategies. By 2012, 28 clinical trials involving gene therapies for neurodegenerative disorders had taken place [229].…”
Section: Cynomolgus Monkeymentioning
confidence: 99%
“…The majority of AAV clinical trials for neurological diseases have used vectors carrying the CMV immediate early promoter followed by a chimeric intron composed of a CMV splice donor and a human globin splice acceptor [113][114][115][116], or a version of the CAG/CBA promoter, described above [117][118][119]. Two other clinical trials have tested AAV vectors carrying mammalian promoters such as the mouse phosphoglycerate kinase (PGK) promoter [120], or the rat neuron-specific enolase (NSE) promoter [121].…”
Section: Challengesmentioning
confidence: 99%
“…Positron emission tomography (PET) of AADC activity has shown newly expressed enzyme in the injected structures and stability of expression over a long period [116]. Also a recent report shows evidence of nerve growth factor (NGF) expression in the post-mortem brain of Alzheimer's patients enrolled in a trial using an AAV2-NGF vector [117].…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation